Coordinated homeostasis of essential mineral nutrients: a focus on iron. (11th November 2020) - Hanikenne, Marc; Esteves, Sara M; Fanara, Steven; Rouached, Hatem
Abstract : We review how regulation of nutrient homeostasis networks is interconnected to determine growth in plants, focusing on iron and its interactions with other macro- and micronutrients. Abstract: In plants, iron (Fe) transport and homeostasis are highly regulated processes. Fe deficiency or excess dramatically limits plant and algal productivity. Interestingly, complex and unexpected interconnections between Fe and various macro- and micronutrient homeostatic networks, supposedly maintaining general ionic equilibrium and balanced nutrition, are currently being uncovered. Although these interactions have profound consequences for our understanding of Fe homeostasis and its regulation, their molecular bases and biological significance remain poorly understood. Here, we review recent knowledge gained on how Fe interacts with micronutrient (e.g. zinc, manganese) and macronutrient (e.g. sulfur, phosphate) homeostasis, and on how these interactions affect Fe uptake and trafficking. Finally, we highlight the importance of developing an improved model of how Fe signaling pathways are integrated into functional networks to control plant growth and development in response to fluctuating environments.